2014
DOI: 10.1021/jz501570m
|View full text |Cite
|
Sign up to set email alerts
|

α-Casein Inhibits Insulin Amyloid Formation by Preventing the Onset of Secondary Nucleation Processes

Abstract: α-Casein is known to inhibit the aggregation of several proteins, including the amyloid β-peptide, by mechanisms that are not yet completely clear. We studied its effects on insulin, a system extensively used to investigate the properties of amyloids, many of which are common to all proteins and peptides. In particular, as for other proteins, insulin aggregation is affected by secondary nucleation pathways. We found that α-casein strongly delays insulin amyloid formation, even at extremely low doses, when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…7 Interestingly, although not directly related to this study, it has been shown in the literature that whey protein α or β caseins, usually present in the form of micelles through mutual hydrophobic and electrostatic interactions, show a chaperone-like activity in inhibiting amyloid beta and insulin from aggregation through mechanisms not yet understood. 37,38 Differently from cell membranes and SDS micelles that are net negative, zwitterionic LPCs readily disperse in water as ultrasmall micelles and subsequent interact with IAPP to halt the latter’s aggregation. Lastly, some LPC species are nearly 5 times more concentrated in the β-cell secretory granules compared to the rest of the cell, and are downregulated some 40–60% after glucose stimulation 39 suggesting a connection between LPC abundance and IAPP activity.…”
Section: Resultsmentioning
confidence: 99%
“…7 Interestingly, although not directly related to this study, it has been shown in the literature that whey protein α or β caseins, usually present in the form of micelles through mutual hydrophobic and electrostatic interactions, show a chaperone-like activity in inhibiting amyloid beta and insulin from aggregation through mechanisms not yet understood. 37,38 Differently from cell membranes and SDS micelles that are net negative, zwitterionic LPCs readily disperse in water as ultrasmall micelles and subsequent interact with IAPP to halt the latter’s aggregation. Lastly, some LPC species are nearly 5 times more concentrated in the β-cell secretory granules compared to the rest of the cell, and are downregulated some 40–60% after glucose stimulation 39 suggesting a connection between LPC abundance and IAPP activity.…”
Section: Resultsmentioning
confidence: 99%
“…6,37,40,48,50 The nucleated aggregation of insulin typically results in an initial at lag phase, followed by a growth phase, and then a saturation phase. It is clear from Fig.…”
Section: The Aggregation Of Insulin At 333 Kmentioning
confidence: 99%
“…It is still under argument that either an intermolecular hydrophobic force or electrostatic attraction is responsible for the amyloidogenesis. It is commonly accepted that fibrillogenesis is commenced due to the partial unfolding of insulin monomers, followed by their association to form protein oligomers and ß-sheet rich amyloid aggregates (Bekard and Dunstan, 2009 ; Librizzi et al, 2014 ). Consequently, understanding of the molecular basis of insulin fibrillation could be of great assessment in the direction of modeling the amyloidogenic pathways and toward developing delivery systems in the treatment of amyloid associated diseases.…”
Section: Introductionmentioning
confidence: 99%